2018
DOI: 10.1111/jgs.15586
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Primary Headache Disorders in Older Adults

Abstract: Objectives To provide a unique perspective on geriatric headache and a number of novel treatment options that are not well known outside of the headache literature. Design Review of the most current and relevant headache literature for practitioners specializing in geriatric care. Results Evaluation and management of headache disorders in older adults requires an understanding of the underlying pathophysiology and how it relates to age‐related physiological changes. To treat headache disorders in general, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 101 publications
(160 reference statements)
0
19
0
4
Order By: Relevance
“…Outside of the realm of physiological changes, it has been suggested that psychological and sociocognitive factors may also account for the relationship between aerobic fitness and migraine. 18 In a longitudinal study using data collected from the Nord-Trøndelag Health Surveys (HUNT study), light exercise 1-3 hours per week and hard physical activity for 1-2 hours per week were associated with reduced risk of migraine. Exercise is also linked to improvements in anxiety and depression among non-clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Outside of the realm of physiological changes, it has been suggested that psychological and sociocognitive factors may also account for the relationship between aerobic fitness and migraine. 18 In a longitudinal study using data collected from the Nord-Trøndelag Health Surveys (HUNT study), light exercise 1-3 hours per week and hard physical activity for 1-2 hours per week were associated with reduced risk of migraine. Exercise is also linked to improvements in anxiety and depression among non-clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…63 Non-pharmacological treatment options such as lifestyle changes should be considered when caring for the older migraine patient. 18 In a longitudinal study using data collected from the Nord-Trøndelag Health Surveys (HUNT study), light exercise 1-3 hours per week and hard physical activity for 1-2 hours per week were associated with reduced risk of migraine. 19 These findings are comparable to our light and strenuous activity results for women; however, it should be noted that while the HUNT study had large proportions of respondents with and without headache who were 50 years of age or older (30.2% and 52.4%, respectively), the HUNT study had a much lower age bound (20 years) than the present study (45 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Headache constitutes one of the main presentation of nervous system primary and secondary disorders (1) . If these conditions are not associated with a clear cause, as a pathology, trauma, or systemic disease, they are named primary headache disorders (2) , which constitute the majority of headache cases (1) . According to the International Classification of Headache Disorders, primary headache disorders can be classified as migraine, tension-type headache (TTH), trigeminal autonomic cephalalgias (as cluster headache, depending on the edition) and other primary headache disorders (3)(4) .…”
Section: Introductionmentioning
confidence: 99%